Silk fibroin-MXene sponge composite material as well as preparation method and application thereof
Through the composite of silk fibroin and MXene nanosheets, a sponge composite with a three-dimensional porous structure is formed, which solves the problem of singularity and irreversible deformation of MXene composite in bone defect repair, and achieves high-quality diffusion rate and repeatable compression performance. It has enhanced its application potential in the treatment of infectious bone defects.
Patent Information
- Application Number
- CN202411366752.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
The existing MXene composites have problems of singularity and irreversible deformation in bone defect repair, and the poor water absorption performance of traditional hydrogels limits their application in the treatment of infectious bone defects.
Silk fibroin-MXene sponge composite material is used to form a three-dimensional porous structure by cross-linking. It has high quality diffusion rate and repeatable compression properties, and is used as a dressing or bone defect repair scaffold.
Improves the biocompatibility and stability of MXene, enhances its application potential in bone repair, provides a multi-purpose treatment plan that can effectively repair trauma infection and bone defects, and has excellent mechanical properties and physiological diffusion. sex.
Smart Images

Figure CN119236174A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of MXene-biopolymer composite materials, and specifically relates to a silk fibroin-MXene sponge composite material and a preparation method and application thereof. Background Art
[0002] The treatment of infected bone defects is currently a difficult and key treatment in the field of orthopedics. When bacteria grow in the bone defect site and are not controlled, the repair and regeneration ability of bone tissue will be further limited. Severe infected bone defects are usually difficult to control infection, have a large defect area, and a complex defect shape, making them particularly difficult to repair. In current clinical practice, antibiotics are the main treatment, but excessive use of antibiotics can lead to the emergence of drug-resistant strains. After the infection is completely eliminated, secondary bone grafting surgery is required, resulting in a long course of treatment and pain for the patient. Therefore, composite materials with both antibacterial and bone repair effects are very necessary for the treatment of infected bone defects.
[0003] MXenes belong to the family of two-dimensional (2D) materials, including a large class of transition metal carbides, nitrides and carbonitrides, which show good functionalization ability due to their rich oxygen-containing groups. In recent years, MXene has shown broad potential in the fields of regenerative medicine and tissue engineering due to its photothermal properties, high hydrophilicity, biodegradability, adsorption selectivity, thermal conductivity, chemical stability, biocompatibility and antibacterial activity. MXene nanosheets show certain antibacterial properties, which can kill bacteria by destroying bacterial cell membranes and inducing oxidative stress. In addition, MXene also has excellent near-infrared light absorption ability and photothermal conversion performance, showing great potential in photothermal therapy.
[0004] However, MXene has a single property when used as a photothermal material for repair. To overcome this single property, it is often compounded with other materials. Traditional MXene composite materials are gel-type. MXene composite hydrogels have poor water absorption properties. Hydrogels with low water content are relatively hard. The strong binding of water molecules to polymer chains limits the elastic deformation of the pores, resulting in poor mass transfer. In addition, hydrogels will undergo irreversible deformation above their yield point and cannot be repeatedly compressed. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a silk fibroin-MXene sponge composite material and a preparation method and application thereof. The silk fibroin-MXene sponge composite material provided by the present invention has a high mass diffusion rate and can be repeatedly compressed.
[0006] In order to achieve the above object, the present invention provides the following scheme:
[0007] The present invention provides a silk fibroin-MXene sponge composite material, comprising a MXene nanosheet and silk fibroin wrapped on the surface of the MXene nanosheet; the silk fibroin is cross-linked to form a three-dimensional porous structure.
[0008] Preferably, the mass ratio of the MXene nanosheets to the silk fibroin is (1-8):70.
[0009] The present invention provides a method for preparing the silk fibroin-MXene sponge composite material described in the above scheme, comprising the following steps:
[0010] The silk fibroin solution, the MXene dispersion and the cross-linking agent are mixed and cross-linked to obtain the silk fibroin-MXene sponge composite material.
[0011] Preferably, the mass content of silk fibroin in the silk fibroin solution is 5-10%; and the concentration of the MXene dispersion is 10 mg / mL.
[0012] Preferably, the volume ratio of the silk fibroin solution to the MXene dispersion is 1:(0.1-0.8).
[0013] Preferably, the cross-linking agent includes 1,4-butanediol diglycidyl ether.
[0014] Preferably, the mass ratio of the cross-linking agent to the volume ratio of the silk fibroin solution is (40-60) mg:1 mL.
[0015] Preferably, the cross-linking time is 3 to 8 minutes.
[0016] Preferably, after the cross-linking is completed, the obtained mixed solution is further subjected to freezing, thawing and dialysis in sequence.
[0017] The present invention provides the use of the silk fibroin-MXene sponge composite material described in the above scheme or the silk fibroin-MXene sponge composite material prepared by the preparation method described in the above scheme in preparing a dressing or in preparing a tissue engineering scaffold.
[0018] The present invention provides a silk fibroin-MXene sponge composite material, comprising a MXene nanosheet and silk fibroin wrapped on the surface of the MXene nanosheet; the silk fibroin is cross-linked to form a three-dimensional porous structure. The porous continuous phase skeleton of the silk fibroin-MXene sponge composite material provided by the present invention facilitates long-range compression, allowing water to flow freely, thereby having a high mass diffusion rate; the sponge can be repeatedly compressed, and the compression deformation can reach more than 80%.
[0019] The present invention uses silk fibroin to wrap MXene nanosheets, which can better control the release of MXene nanosheets compared to traditional MXene film materials, while ensuring the effect of MXene and improving its biocompatibility and stability. In addition, the silk fibroin-MXene sponge composite material has a 3D porous morphology, which can be used not only as a dressing for wound infection repair but also as a supporting material for bone defect repair, and has multiple uses.
[0020] The present invention provides a method for preparing the silk fibroin-MXene sponge composite material described in the above scheme. In the present invention, the silk fibroin wrapped MXene nanosheet forms a porous sponge scaffold with excellent mechanical properties under the action of a crosslinker (due to the presence of an epoxy compound, i.e., a crosslinker, a three-phase system consisting of silk fibroin, water and epoxy compounds is formed. This three-phase system undergoes heat-induced phase separation during the cooling process (i.e., freezing). In the phase separation process, hydrogen bonds are formed between some silk fibroin molecular chains, and the hydrogen bonds between molecules hinder the hydrogen bonds within the molecules, so that the original strong intramolecular bonds are reduced or weakened. Therefore, the crosslinker, such as 1,4-butanediol diglycidyl ether, has a reduced thermal decomposition temperature, a faster dissolution rate, and a reduced stability, so that the silk fibroin is cross-linked to form a three-dimensional porous structure), compared to other traditional gel-based MXene composite materials, it has higher porosity, water absorption and better compression performance. It can withstand heavy loads when used for bone repair, and due to its porous structure, it exhibits the diffusibility of physiological substances, which is more conducive to cell adhesion and the penetration of nutrients.
[0021] The present invention uses MXene as a photothermal agent to achieve the effect of heating and sterilization. Compared with graphene as a photothermal agent, MXene contains metal ions such as titanium, which has better properties in promoting osteogenesis. In addition, MXene has a large amount of oxygen, fluorine and hydroxyl groups on its surface, which makes it more hydrophilic.
[0022] The silk fibroin provided by the present invention is used as a scaffold base material. Compared with other non-biological polymers wrapped in MXene, silk fibroin can cooperate with MXene to repair bones and skin because of its structure composed of amino acids. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0024] Figure 1The light-heat curves of the materials obtained in Examples 1 to 3 of the present invention and Comparative Example 1;
[0025] Figure 2 This is a plate colony picture of the material obtained in the present invention;
[0026] Figure 3 is the bacterial mortality rate (LDH release) of the material obtained in the present invention;
[0027] Figure 4 is the porosity of the materials obtained in Examples 1 to 3 of the present invention and Comparative Example 1;
[0028] Figure 5 is the water absorption rate of the materials obtained in Examples 1 to 3 of the present invention and Comparative Example 1;
[0029] Figure 6 The stress-strain curves of the materials obtained in Examples 1 to 3 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0030] The present invention provides a silk fibroin-MXene sponge composite material, comprising a MXene nanosheet and silk fibroin wrapped on the surface of the MXene nanosheet; the silk fibroin is cross-linked to form a three-dimensional porous structure.
[0031] In the present invention, the mass ratio of the MXene nanosheets to the silk fibroin is preferably (1-8):70, and more preferably (2-6):70.
[0032] The porous continuous phase skeleton of the silk fibroin-MXene sponge composite material provided by the present invention facilitates long-range compression, allowing water to flow freely, thereby having a high mass diffusion rate; the sponge can be compressed repeatedly, and the compression deformation can reach more than 80%.
[0033] The present invention uses silk fibroin to wrap MXene nanosheets, which can better control the release of MXene nanosheets compared to traditional MXene film materials, while ensuring the effect of MXene and improving its biocompatibility and stability. In addition, the silk fibroin-MXene sponge composite material has a 3D porous morphology, which can be used not only as a dressing for wound infection repair but also as a supporting material for bone defect repair, and has multiple uses.
[0034] The present invention provides a method for preparing the silk fibroin-MXene sponge composite material described in the above scheme, comprising the following steps:
[0035] The silk fibroin solution, the MXene dispersion and the cross-linking agent are mixed and cross-linked to obtain the silk fibroin-MXene sponge composite material.
[0036] Unless otherwise specified, the materials and equipment used in the present invention are commercially available.
[0037] In the present invention, the method for preparing the silk fibroin solution preferably comprises the following steps: subjecting silk to degumming, lithium bromide dissolution, dialysis, freeze-drying and redissolution to obtain the silk fibroin solution.
[0038] Specifically, the raw silk of silkworms is degummed in a sodium carbonate aqueous solution, and the silk is stirred every 5 minutes, then the silk is taken out and rinsed with pure water for 3 times, and placed in a fume hood for ventilation and drying to obtain dried silk fibroin;
[0039] The dried silk fibroin is placed in a lithium bromide solution until it is completely dissolved, the lithium bromide solution in which the silk fibroin is dissolved is poured into a dialysis bag of 8000-14000D, and dialyzed in deionized water for 3 days, with the water changed every 5 hours, the solution after the dialysis is centrifuged at 8000 rpm for 3 times to remove impurities to obtain a silk fibroin solution, and then the silk fibroin solution is frozen at -20°C overnight, and then freeze-dried to obtain a silk fibroin solid;
[0040] The silk fibroin solid is mixed with water to dissolve, thereby obtaining the silk fibroin solution.
[0041] In the present invention, the volume ratio of the mass of the raw silk of Bombyx mori to the sodium carbonate solution is preferably 1 g:50 mL; the mass content of sodium carbonate in the sodium carbonate solution is preferably 0.5%; the temperature of the degumming treatment is preferably 100° C., and the time is preferably 30 min.
[0042] In the present invention, the volume ratio of the mass of the dried silk fibroin to the lithium bromide solution is preferably 1 g:5 mL; the molar concentration of the lithium bromide solution is preferably 9.3 mol / L; and the temperature of the lithium bromide solution is preferably 60°C.
[0043] The raw material used in the present invention is silk fibroin from silk, which contains both hydrophilic blocks rich in tyrosine and glycine and hydrophobic blocks rich in alanine and glycine, thereby producing an overall hierarchical design of silk fibroin. These blocks are composed of various secondary structures generated by hydrogen bonding between chains, which determine the size of each block and the final mechanical strength. Due to its unique chemical design and diversified multi-domain composition, silk fibroin can interact with heterogeneous inorganic fillers through static electricity, van der Waals forces and hydrogen bonds of different blocks; silk fibroin is a natural polymer protein rich in 18 kinds of amino acids, and silk fibroin materials have strong adhesion to various cells such as vascular endothelial cells, fibroblasts, bone marrow mesenchymal stem cells and osteoblasts, and can guide cell migration and support cell proliferation. When the three-dimensional scaffold and fiber mesh based on silk fibroin are used for in situ guided regeneration of vascularized tissues such as skin dermis and bone, they show strong ability to enrich vascular endothelial cells and promote vascularization in the scaffold, which is conducive to providing oxygen and nutrition for the growth of tissue repair cells, thereby promoting the regeneration and repair of defective tissues such as vascularized bone.
[0044] In the present invention, the method for preparing the MXene dispersion preferably comprises the following steps:
[0045] Mixing LiF and HCl solutions to perform double decomposition reaction to obtain HF solution;
[0046] Ti3AlC2 and the HF solution are mixed to carry out an etching reaction, and then the resulting slurry is centrifuged at 3500rpm for 5min, repeated 7 to 8 times until the pH value reaches 6, and then vacuum filtered; the precipitate after vacuum filtration is centrifuged continuously until a viscous precipitate appears and the upper liquid turns black, then the centrifugation is stopped, the upper liquid is poured out, and then deionized water is added to the resulting precipitate, mixed under an inert atmosphere, the resulting reaction liquid is ultrasonicated for 1h, and then the resulting liquid is centrifuged at 3000rpm for 30min, and the resulting supernatant is the MXene dispersion.
[0047] In the present invention, the mass ratio of LiF to the volume of HCl solution is preferably 3.2 g:40 mL; the molar concentration of the HCl solution is preferably 9 mol / L; the temperature of the double decomposition reaction is preferably 40° C., and the time is preferably 15 min.
[0048] In the present invention, the mass ratio of Ti3AlC2 and LiF is preferably 2:3.2; the temperature of the etching reaction is preferably 40-45°C, and the time is preferably 48h; the etching reaction is preferably carried out under stirring, and the stirring speed is preferably 500rpm.
[0049] After obtaining the silk fibroin solution and the MXene dispersion, the present invention mixes the silk fibroin solution, the MXene dispersion and a cross-linking agent, and performs cross-linking to obtain the silk fibroin-MXene sponge composite material.
[0050] In the present invention, the mass content of silk fibroin in the silk fibroin solution is preferably 5-10%, more preferably 6-9%; the concentration of the MXene dispersion is preferably 10 mg / mL. In the present invention, the volume ratio of the silk fibroin solution to the MXene dispersion is preferably 1:(0.1-0.8), more preferably 1:(0.2-0.4).
[0051] In the present invention, the cross-linking agent preferably includes 1,4-butanediol diglycidyl ether; the volume ratio of the mass of the cross-linking agent to the silk fibroin solution is preferably (40-60) mg:1 mL, and more preferably (45-55) mg:1 mL.
[0052] In the present invention, the cross-linking time is preferably 3 to 8 minutes, more preferably 3.5 to 6.5 minutes; the cross-linking temperature is preferably room temperature; the cross-linking is preferably carried out under stirring; and the stirring speed is preferably 200 rpm.
[0053] After the cross-linking is completed, the method further includes sequentially freezing, thawing and dialyzing the obtained mixed solution.
[0054] In the present invention, the freezing temperature is preferably -20°C, and the time is preferably 4 hours; the dialysis is preferably in pure water, and the dialysis time is preferably 3 days. The present invention can wash away the cross-linking agent through dialysis.
[0055] In the present invention, the silk fibroin-wrapped MXene nanosheets form a porous sponge scaffold with excellent mechanical properties under the action of a crosslinking agent. Compared with other traditional gel-based MXene composite materials, it has higher porosity, water absorption and better compression performance. When used for bone repair, it can withstand heavy loads, and due to its porous structure, it exhibits the diffusivity of physiological substances, which is more conducive to cell adhesion and the penetration of nutrients.
[0056] The present invention provides the use of the silk fibroin-MXene sponge composite material described in the above scheme or the silk fibroin-MXene sponge composite material prepared by the preparation method described in the above scheme in preparing a dressing or in preparing a tissue engineering scaffold.
[0057] The present invention uses MXene as a photothermal agent to achieve the effect of heating and sterilization. Compared with graphene as a photothermal agent, MXene contains metal ions such as titanium, which has better properties in promoting osteogenesis. In addition, MXene has a large amount of oxygen, fluorine and hydroxyl groups on its surface, which makes it more hydrophilic.
[0058] The silk fibroin provided by the present invention is used as a scaffold base material. Compared with other non-biological polymers wrapped in MXene, silk fibroin can cooperate with MXene to repair bones and skin because of its structure composed of amino acids.
[0059] In order to further illustrate the present invention, a silk fibroin-MXene sponge composite material provided by the present invention and its preparation method and application are described in detail below in combination with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.
[0060] Examples 1 to 3
[0061] Preparation of silk fibroin solution
[0062] The silk was degummed, dissolved in lithium bromide, dialyzed, freeze-dried, and re-dissolved to prepare a silk fibroin solution. Specifically, the raw silk of the silkworm was placed in a 100°C boiling water with a mass fraction of 0.5% sodium carbonate at a ratio of 1:50 (mass to volume ratio) for degumming for 30 minutes, and the silk was stirred once every 5 minutes. After that, the silk was taken out and rinsed with pure water for 3 times, and placed in a fume hood for ventilation and drying. The ventilated and dried silk fibroin was placed in a 60°C, 9.3 mol / L lithium bromide solution at a ratio of 1:5 (mass to volume ratio) until it was completely dissolved. The lithium bromide solution in which the silk fibroin was dissolved was poured into a dialysis bag of 8000-14000D, dialyzed in deionized water for 3 days, and the water was changed every 5 hours. The solution after dialysis was centrifuged at 8000rpm for 3 times in a high-speed centrifuge to remove impurities and obtain a silk fibroin solution. Finally, the silk fibroin solution was placed in a -20°C refrigerator overnight and freeze-dried to obtain a silk fibroin solid. 80 mg of the silk fibroin solid was dissolved in 1 mL of pure water to prepare a silk fibroin solution.
[0063] Preparation of MXene dispersion
[0064] Add 3.2g of LiF and 40mL of 9mol / L HCl solution to the polytetrafluoroethylene kettle, and react at 40℃ for 15min (to fully react LiF); weigh 2g of Ti3AlC2 and add it to the kettle in small amounts (about 10min), adjust the reactor speed to 500rpm, and react at 40-45℃ for 48h; after the reaction, pour the above slurry into two centrifuge tubes, centrifuge at 3500rpm for 5min, repeat 7-8 times until the pH reaches 6, and then vacuum filter. Add the precipitate after vacuum filtration back to the centrifuge tube, continue centrifugation until a viscous precipitate appears and the upper liquid turns black, then stop centrifugation and pour out the upper liquid; add 50mL of deionized water to the two centrifuge tubes, pour them into a three-mouth round-bottom flask, one mouth is passed with inert gas, one mouth is used to fix the bracket (blocking), and the last mouth is blocked after passing the atmosphere. Place the above device in an ultrasonic machine with ice packs for 1h. After the ultrasound, the liquid was poured into a centrifuge tube and centrifuged at 3000 rpm for 30 min to obtain a dark green MXene dispersion with a concentration of 10 mg / mL.
[0065] Slowly add different volumes of 10 mg / mL MXene dispersion to the silk fibroin solution to obtain different concentrations of MXene mixed solutions (the concentrations of MXene in the mixed solution are 2 mg / mL, 4 mg / mL, and 8 mg / mL, respectively), and stir continuously, and finally slowly add 50 μL (55 mg) of 1,4-butanediol diglycidyl ether, and stir continuously. Put the prepared mixed solution into a -20°C refrigerator and freeze it for 4 hours, then thaw it, and finally put the prepared sponge material (solid) into pure water for dialysis for 3 days to obtain the silk fibroin-MXene sponge composite material.
[0066] Comparative Example 1
[0067] The preparation steps are the same as those in Example 1, except that no MXene dispersion is added, that is, the concentration of MXene in the mixed solution is 0 mg / mL.
[0068] Example 4
[0069] The preparation process of MXene (10 mg / mL) solution and silk fibroin solution was the same as in Example 1;
[0070] Material preparation: 80 mg of silk fibroin was dissolved in 1 mL of pure water to prepare a silk fibroin solution, 400 μL of 10 mg / mL MXene dispersion was slowly added thereto, and stirring was continued, and finally 50 μL of 1,4-butanediol diglycidyl ether was slowly added, and stirring was continued. The prepared mixed solution was placed in a -20°C refrigerator and frozen for 4 hours, then thawed, and finally the prepared sponge material was placed in pure water for 3 days for dialyzing, and the silk fibroin-MXene sponge composite material was obtained;
[0071] Performance Testing
[0072] The porosity, water absorption and compression performance of the materials obtained in Examples 1 to 3 and Comparative Example 1 were tested. The results are as follows: Figures 4 to 6 And Tables 1-2.
[0073] Table 1 Porosity of materials obtained in Examples 1 to 3 and Comparative Example 1 (%)
[0074] serial number SF 0.2%MXene / SF 0.4%MXene / SF 0.8%MXene / SF Porosity 1 95 90 93 90 Porosity 2 93 92 94 93 Porosity 3 88 93 95 95
[0075] Table 2 Water absorption of materials obtained in Examples 1 to 3 and Comparative Example 1
[0076] serial number SF 0.2%MXene / SF 0.4%MXene / sf 0.8%MXene / SF Water absorption rate 1 1300% 1310% 1432% 1450% Water absorption 2 1339% 1348% 1380% 1421% Water absorption rate 3 1350% 1432% 1358% 1389%
[0077] In Tables 1-2, (SF, 0.2% MXene / SF, 0.4% MXene / SF and 0.8% MXene / SF correspond to the concentrations of MXene in the mixed solutions of Examples 1-3, which are 0 mg / mL, 2 mg / mL, 4 mg / mL and 8 mg / mL respectively).
[0078] From Tables 1 to 2 and Figures 4 to 6 It can be seen that the silk fibroin-MXene sponge composite material prepared by the present invention has higher porosity, water absorption and better compression performance.
[0079] Photothermal experiment 1: using infrared laser 0.65W / cm 2 The composite materials with different MXene concentrations obtained in Examples 1 to 3 and Comparative Example 1 were irradiated at a distance of 10 cm, and the temperature change was recorded every 30 seconds. The temperature rise curve was plotted using Orijin. Figure 1 .
[0080] like Figure 1 As shown (the concentrations of MXene in the mixed solution are 0 mg / mL, 2 mg / mL, 4 mg / mL, and 8 mg / mL, respectively) Figure 1The change of photothermal temperature is related to the concentration of MXene, showing a proportional relationship, which further illustrates the photothermal effect of MXene.
[0081] Photothermal experiment 2: The material was co-cultured with Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), and methicillin-resistant Staphylococcus aureus (MRSA) in a 48-well plate and the cells were illuminated with an infrared laser at a power of 0.5 W / cm 2 , irradiate the silk fibroin-MXene sponge composite material at a distance of 10 cm, and control the maximum temperature of the composite material at about 52 °C. The co-culture solution after illumination is diluted with PBS solution for 10 3 times, spread on LB solid medium and culture at 37℃ for 24h. Figure 2 shown.
[0082] Depend on Figure 2 From the plate colony pictures shown, it can be seen that compared with the Control group, the SF group (pure silk fibroin solution, comparative example 1) has no obvious antibacterial effect, MXene has a certain antibacterial effect, but it is far from reaching the antibacterial index, and the 0.4% MXene / SF+NIR group shows excellent antibacterial performance, and the antibacterial rate against the three bacteria is above 99%.
[0083] Photothermal experiment 3: The material was co-cultured with Escherichia coli (E. coli), Staphylococcus aureus (S. aureus) and methicillin-resistant Staphylococcus aureus (MRSA) in a 48-well plate. The infrared laser was used at a power of 0.5 W / cm 2 , irradiate the silk fibroin / MXene sponge material at a distance of 10 cm, and keep the maximum temperature of the material at about 52°C. Use the lactate dehydrogenase (LDH) activity detection kit to determine the degree of bacterial cell membrane damage. According to the instructions, in short, the bacterial culture fluid co-cultured with the scaffold and irradiated with the LDH detection working solution was incubated at room temperature in the dark for 30 minutes, and the sample absorbance was measured at a wavelength of 390nm to represent LDH release.
[0084] Figure 3The bacterial mortality rate (LDH release) of the material obtained by the present invention. The degree of bacterial cell membrane damage was determined by LDH release detection. The results showed that the bacterial mortality rate of the Control and SF groups was the lowest; the bacterial mortality rate of MXene / SF reached 30%, which was higher than that of the Control and SF groups; the bacterial mortality rate of MXene+NIR / SF was above 90%, which was significantly higher than that of other groups.
[0085] In photothermal experiments 2 to 3, the Control group means that no light is required and only the corresponding bacteria group is added;
[0086] Control+NIR group, representing 808 nm light exposure;
[0087] SF group, representing the material obtained in Comparative Example 1, without light exposure;
[0088] SF+NIR group, representing the material obtained in comparative example 1 was irradiated with 808 nm light;
[0089] MXene group, representing the 10 mg / mL MXene dispersion obtained in Example 1, without light exposure;
[0090] MXene+NIR group, representing the 10 mg / mL MXene dispersion obtained in Example 1, subjected to 808 nm illumination;
[0091] The MXene / SF+NIR group represents the material obtained in Example 4 and is irradiated with 808 nm light.
[0092] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A silk fibroin-MXene sponge composite material, comprising MXene nanosheets and silk fibroin wrapped on the surface of the MXene nanosheets; the silk fibroin is cross-linked to form a three-dimensional porous structure.
2. The silk fibroin-MXene sponge composite material according to claim 1, characterized in that: The mass ratio of the MXene nanosheets to the silk fibroin is (1-8):
70.
3. The method for preparing the silk fibroin-MXene sponge composite material according to any one of claims 1 or 2, comprising the following steps: The silk fibroin solution, the MXene dispersion and the cross-linking agent are mixed and cross-linked to obtain the silk fibroin-MXene sponge composite material.
4. The preparation method according to claim 3, characterized in that: The mass content of silk fibroin in the silk fibroin solution is 5-10%; the concentration of the MXene dispersion is 10 mg / mL.
5. The preparation method according to claim 3 or 4, characterized in that: The volume ratio of the silk fibroin solution to the MXene dispersion is 1:(0.1-0.8).
6. The preparation method according to claim 3, characterized in that: The cross-linking agent includes 1,4-butanediol diglycidyl ether.
7. The preparation method according to claim 3 or 6, characterized in that: The mass ratio of the cross-linking agent to the volume ratio of the silk fibroin solution is (40-60) mg:1 mL.
8. The preparation method according to claim 3 or 6, characterized in that: The cross-linking time is 3 to 8 minutes.
9. The preparation method according to claim 3, characterized in that: After the cross-linking is completed, the method further includes sequentially freezing, thawing and dialyzing the obtained mixed solution.
10. Use of the silk fibroin-MXene sponge composite material according to claim 1 or 2 or the silk fibroin-MXene sponge composite material prepared by the preparation method according to any one of claims 3 to 9 in preparing dressings or in preparing tissue engineering scaffolds.
Citation Information
Cited By
MXene-SS / SF composite material and preparation method and application thereof
CN119823582A